Determination of Metastable Zone Width, Induction Period and Interfacial Energy of a Ferroelectric Crystal - Potassium Ferrocyanide Trihydrate (KFCT) - R. Kanagadurai; R. Durairajan; R. Sankar; G. Sivanesan; S. P. Elangovan; r. jayavel (E-Journal of Chemistry)
An order-disorder type potassium ferrocyanide trihydrate (KFCT) is a coordination compound forming lemon- yellow monoclinic ferroelectric crystals with curie temperature 251 K. KFCT crystals have been grown by temperature lowering solution growth technique. Solubility of KFCT has been determined for various temperatures. Metastable zone width, induction period and interfacial energy were determined for the aqueous solution of KFCT. Bulk crystal of potassium ferrocyanide trihydrate was grown with the optimized growth parameters. The grown crystal possesses good optical transmission in the entire UV-Visible region